Research of Logic Threshold Control of Parallel Hybrid Electric Vehicle Clutch - Zhang Xuesong; Li Xueting; Liu Youpeng (Jixie chuandong)
By studying the clutch of parallel hybrid electric vehicle,the state judgment model and working process model based on logic threshold control strategy are established. The operation control principle of clutch in parallel hybrid electric vehicle is analyzed and the control model is set up. The feasibility of the logic threshold control in the clutch control of parallel hybrid electric vehicle is simulated on the Matlab/Simulink platform about clutch state judgment and working process. The result shows that the logic threshold control strategy can effectively judge the working state of the clutch,and then perform the work of shifting,braking and energy switching of the clutch in the parallel hybrid electric vehicle.